Relational factors predict telepsychotherapy acceptance in patients: The role of therapeutic relationship and attachment - V. Békés; K. Aafjes-Van Doorn (European Psychiatry, 2022)
Introduction During the early months of the COVID-19 pandemic, patients receiving individual psychotherapy needed to transition to telepsychotherapy (TP). Since telemental health appears to be here to stay after the pandemic ends, it is crucial to understand factors that determine whether telemental health is a good fit for patients.